"It is like diversity to unity" A case study exploring how party members of Myanmar's two largest parties think about inclusion of its citizens in the democratic process - Karlsson,Karin (2014)
This study explores how members of Myanmar’s largest political parties perceive inclusion of its citizen in the democratic process. Through a threefold aim the study has looked at how party members’ understanding of inclusion is externalised within the parties; whether these perceptions implies hindrances to Myanmar’s democratic development; and how the analytical findings can contribute to the theoretical discourse. The study was carried out as a qualitative case study. Guided by theory on cultures of organisations, primary data was mainly collected in Yangon through semi-structured individual interviews with party members holding various positions within the parties. The prolonged time spent in the field provided the study with observations that validated information attained through the interviews. By exploring inclusion in relation to the theoretical notions of representation, participation and deliberation a broader understanding of the respondents’ perceptions was obtained. The analysis found that while inclusion in general is understood as something positive, it is also understood as a means to win elections. An understanding that in turn can lead to merely symbolic inclusion of different groups in society. Further on, the analysis found that a contextual deployment of the ‘participation paradox’ could enable identification of participation barriers relevant for diverse settings.
Keywords: Deliberation; Democracy; Democratic Development; Diversity; Inclusion; Myanmar; Participation; Participation Paradox; Representation